Fecal bile acid profiles before and after fecal microbial transplant in pediatric onset ulcerative colitis - Kathleen Lo; Patil Kavarian; Beibei Wang; Riddhi Parsana; Ramon Durazo-Arvizu; Fengzhu Sun; Sonia Michail (Gut Microbes Reports)
Fecal bile acids (BAs) are key metabolites altered in patients with inflammatory bowel disease (IBD), therefore serving as potential targets of fecal microbial transplant (FMT). To compare changes in fecal BA composition and corresponding microbial transformation pathways in pediatric ulcerative colitis (UC) patients before and after FMT for up to 48 weeks. Fecal BAs, as well as enzymes and bacteria related to BA metabolism were measured in 28 healthy children, and 48 children with mild to moderate UC before and after FMT. Several primary BAs were higher in UC patients at baseline, and subsequently decreased over the 48 weeks following FMT. In particular, the primary BA cholic acid (CA) was higher in UC children at baseline (11.73 pg/mg) compared to healthy controls (8.47 pg/mg), decreased to 10.82 pg/mg at 4 weeks post FMT (p = 0.001) then 10.07 pg/mg at 48 weeks (p = 0.077). Following FMT, the ratio of secondary to primary BAs became more similar to healthy children. The genes coding for bile salt hydrolase, 7α/β-hydroxysteroid dehydrogenase, and bile acid induced operon enzymes were lower in UC patients at baseline, with the majority of them increasing following FMT. Similarly, many of the bacterial genera involved in bile acid metabolism had corresponding increases after FMT.